Pengembangan Usaha Mikro Kecil Menengah Melalui Pembuatan E-Katalog Di Kerajinan Tenun Ikat Medali Mas Bandar Kidul Kota Kediri - Pratiwi, Dinda Ayu; Abidah, Dliyaul; Ilhami, Femilia Hajar; Husna, Fithiyyatul; Farida, Nur Alfi Fitri; Ariyanti, Meika Putri; Munawaroh, Siti Lailatul; Putri, Whenika; Afandi, Akhmad Jazuli (Welfare : Jurnal Pengabdian Masyarakat, 2024)
The Medali Mas ikat weaving craft in Bandar Kidul, Kediri City, is one of the creative economic sectors that has great potential to be developed. However, limitations in product marketing and promotion are the main obstacles to sustainability and increasing business competitiveness. This community service activity aims to increase the capacity of Medali Mas micro, small and medium enterprises (MSMEs) through the development of e-catalogs as a modern promotional media. The implementation method uses the ABCD (Asset-Based Community Development) approach, which involves identifying local potential, training in creating e-catalogs, and digital marketing assistance. The results of the activity show that the e-catalog has succeeded in increasing product visibility and simplifying the marketing process. Evaluation shows an increase in transactions of up to 30% after implementing the e-catalog. This program proves the importance of digital technology in supporting the transformation of traditional MSMEs towards a wider and more competitive market.